MINIMALLY INVASIVE SURGERY FOR CONGENITAL HYDRONEPHROSIS IN CHILDREN - Anna Kadar; Lorena Vatra; Marcel Oancea (Amaltea Medical Publishing House, 2016)
Introduction. Minimal invasive treatment for congenital hydronephrosis in children remains a controversial topic, both in defining the necessity and timing of operation using laparoscopic techniques in neonates and infants. Materials and methods. This study aims to analyze criteria used for surgery in a series of patients operated in a laparoscopic manner, for congenital hydronephrosis, at the Emergency Clinical Hospital for Children "Marie Curie" Bucharest, Department of Pediatric Surgery, between 2007-2015. Results. In our series, the most frequent found criteria for surgery were anterior-posterior diameter over 3 cm, followed by 50% reduced parenchymal thickness, decreased renal function under 40% and finally symptomatic criteria - urinary tract infections and flank colicky pain. Both pelvic dilatation and parenchymal thickness correlates with renal function, though reduced parenchymal thickness has a stronger correlation. Infants under 1 year and under 10 kg represented a significant proportion (17.5% and 22.5% respectively). Conclusions. Young age (under 1 year old) and low-weight (under 10 kilos) in children are not reasons to delay classical or laparoscopic surgical treatment for PUJO (pyelo-ureteric junction obstruction). Pyelectasis is not specific to PUJO. It does not always mean obstruction and does not always show a strong correlation with impaired renal function. Best in establishing therapeutic conduct are the magnitude of renal parenchymal restructuring, the degree of renal function impairment and clinical symptomatology. Laparoscopic treatment is an effective surgical approach, that meets all the major advantages of minimal invasive surgery, applicable to infants and small children, regardless of age and weight.